União conjugal heterossexual e homoafetiva de idosos brasileiros: antigos conceitos, novas concepções - Higa, Joelma (2013)
This research investigates heterosexual and homosexual marriages in old age. We hypothesized that keep actions invisible protagonists conjugalities strengthens the homogenization and generalization attributes of individuals, increasing prejudice and stereotypical thinking that ignores the dignity and rights of the elderly. The aim is capture the diversity in marriages in old age by mapping profile with the collection of data from IBGE and understand the speech of subjects through a TV show and a movie that address.In the long run, the study may contribute to programs of social policies that consider sexual diversity. The research followed the quantitative and qualitative methods, in view that you want to analyze the data collected, crossing with the discourses of the subject, to enable closer to the reality of those who experience this situation